SOCIAL NETWORKS USED AS A STRATEGIC INSTRUMENT FOR COMPETITIVE INTELLIGENCE - Borges, Paulo Cesar Rodrigues; Vítola, Letícia de Oliveira; Iglesias, Ricardo Dutra (Revista Coleta Científica, 2021)
This is a review of the article entitled “Social networks as a strategic tool for competitive intelligence”. This article was written by Adriana Rosecler Alcará; Elaine Cristina Liviero Tanzawa; Ivone Guerreiro Di Chiara; Maria Inês Tomaél; Plínio Pinto de Mendonça Uchoa Junior; Valéria Cristina Heckler; Jorge Luis Rodrigues; Sulamita da Silva Valente. The article reviewed here was published in the journal “TransInformação - Pontifícia Universidade Católica de Campinas”, no Ano 2006, Vol.18, n.2